Brothers in arms : the unique collection of letters and photographs from two brothers at the Front during the first World War - Farrington, Karen (Pen & Sword Military, 2015)
Hidden away in the back of an old desk drawer was a dusty pile of school-style exercise books. In them were the recollections of a young officer who had fought with the Essex Regiment in the First World War from the Battle of Neuve Chapelle in 1915, through the mud and misery of Ypres, to see victory in 1918. Discovering the memoirs of Lieutenant Robert D'Arblay Gybbon-Monypenny was not the only surprise, what was even more remarkable was how well-written they were, how vividly life and death in the trenches was portrayed.That life in the trenches saw Robert hit by a sniper's bullet, buried.